Comprehensive Management of Acute Ischemic Stroke in Psoriatic Patient - Al Rasyid; Taufik Mesiano; Mohammad Kurniawan; Rakhmad Hidayat; Reyhan Eddy Yunus; Endi Novianto; Ocktafiani Ocktafiani; Elvan Wiyarta; Salim Harris (Hindawi Limited, 2023)
Background. Stroke is one of the top causes of death and disability in several nations. Patients with psoriasis are susceptible to multiple comorbidities, including stroke. In addition to acute ischemic stroke, psoriasis and chronic inflammation require comprehensive treatment. Here, we present a comprehensive management case of a patient with an acute ischemic stroke and psoriasis. Case Presentation. A 42-year-old man came to the emergency department complaining of sudden left-sided weakness that started two and a half hours before being admitted to the hospital. The patient was treated with cyclosporine from 2013 to 2019 for a history of psoriasis. The patient was then treated for secondary stroke prevention using aspirin, vitamin B6, vitamin B12, folic acid, simvastatin, cyclosporine, and topical treatment. After two days of treatment, the patient's condition improved clinically, and he was discharged without further neurological deficits. As a home medication, the patient's cyclosporine was switched to the initial dose of methotrexate (7.5 mg/week) and titrated weekly to a response dose of 10 mg in the 10th week. After three months of follow-up, the patient's condition remained stable, devoid of similar symptoms or sequelae. Conclusions. Cyclosporine should only be used for a maximum of 1 year for stroke management with psoriasis and be substituted for other systemic agents such as methotrexate. In addition, anticoagulants, antihypertensive, antihyperlipidemic, vitamin B6, vitamin 12, and folic acid regimens are highly recommended for comprehensive therapy of cardiovascular comorbidities.